2007
DOI: 10.1016/j.psyneuen.2007.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Cellular effects of swim stress in the dorsal raphe nucleus

Abstract: Swim stress regulates forebrain 5-hydroxytryptamine (5-HT) release in a complex manner and its effects are initiated in the serotonergic dorsal raphe nucleus (DRN). The purpose of this study was to examine the effects of swim stress on the physiology of DRN neurons in conjunction with 5-HT immunohistochemistry. Basic membrane properties, 5-HT(1A) and 5-HT(1B) receptor-mediated responses and glutamatergic excitatory postsynaptic currents (EPSCs) were measured using whole-cell patch clamp techniques. Rats were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 43 publications
1
33
0
1
Order By: Relevance
“…Glutamate neurotransmission within the DRN has been implicated in the pathophysiology of affective disorders, such as depression (Paris and Cunningham, 1994;Grahn et al, 2000;Paul and Skolnick, 2003) and stress (Amat et al, 2005;Kirby et al, 2007). Indeed, in humans and animal models, glutamate receptor antagonists have been reported to be effective antidepressants (Trullas and Skolnick, 1990;Yilmaz et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate neurotransmission within the DRN has been implicated in the pathophysiology of affective disorders, such as depression (Paris and Cunningham, 1994;Grahn et al, 2000;Paul and Skolnick, 2003) and stress (Amat et al, 2005;Kirby et al, 2007). Indeed, in humans and animal models, glutamate receptor antagonists have been reported to be effective antidepressants (Trullas and Skolnick, 1990;Yilmaz et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Subdivisions of the DRN innervate distinct targets and receive disparate afferent inputs (Abrams et al, 2004;Lee et al, 2005Lee et al, , 2007Hale et al, 2008), including 5-HTergic interactions within the DRN (Lemos et al, 2006;Kirby et al, 2007). Neurons in the DRL have been deemed to play a distinctive, crucial role in the response to stressors.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioral studies demonstrated differences in all three major monoaminergic systems; that is, dopamine, norepinephrine, and serotonin (Conti et al, 1997;Lopez-Rubalcava and Lucki, 2000;Pare and Tejani-Butt, 1996;Pearson et al, 2006;Tejani-Butt et al, 1994). The DRN is critical in mediating responses to uncontrollable stress (Maier and Watkins, 2005) and is functionally altered following in vivo stressor exposure (Kirby et al, 2007;Price et al, 2002). We, therefore, focused our attention to differences in mRNA expression, protein expression, and physiology in the DRN of WKY rats.…”
Section: Discussionmentioning
confidence: 99%